Decision Support System for Integrated Pastoral Program Planning with The Church Information System of Santa Veronika Kaiwatu Parish Using The Simple Additive Weighting Method - Jufinety Langi; Angelo Rumondor; Gerald Mamangkey; Fitria Claudya Lahinta; Betsy Rooroh (International Journal Labs, 2026)
Pastoral program planning is a critical function in Roman Catholic parishes; however, many rely on subjective judgment and manual scoring, resulting in inconsistent prioritization of programs. This study aims to design, implement, and evaluate a web-based Decision Support System (DSS) integrated with the Santa Veronika Kaiwatu Parish information system, using the Simple Additive Weighting (SAW) method to optimize pastoral program selection. The system evaluates twelve program alternatives across six criteria: spiritual impact, community reach, resource availability, urgency, sustainability, and administrative feasibility. The methodology includes database integration, PHP-based SAW computation, and User Acceptance Testing (UAT) with fifteen parish staff and council members. Results indicate zero deviation in SAW calculations compared to manual reference scores, confirming computational accuracy. Performance testing shows response times under 1.2 seconds for up to twenty alternatives, validating system efficiency. UAT results demonstrate high user satisfaction (mean score 4.31/5), highlighting ease of use, interface clarity, and transparency in ranking results. These findings suggest that the integrated DSS effectively enhances decision-making, resource allocation, and stakeholder confidence in program prioritization. In conclusion, the SAW-based DSS provides a replicable model for parish administration. Future research may explore advanced multi-criteria decision-making (MCDM) techniques and predictive analytics to further improve planning accuracy and scalability in multi-parish contexts.